2020
DOI: 10.3390/jcm9082568
|View full text |Cite
|
Sign up to set email alerts
|

Modified Split-Scan Computed Tomography (CT) Diagnostics of Severely Injured Patients: First Results from a Level I Trauma Center Using a Dedicated Head-and-Neck CT-Angiogram for the Detection of Cervical Artery Dissections

Abstract: Introduction: Traumatic cervical artery dissections are associated with high mortality and morbidity in severely injured patients. After finding even higher incidences than reported before, we decided to incorporate a dedicated head-and-neck computed tomography angiogram (CT-A) in our imaging routine for patients who have been obviously severely injured or, according to trauma mechanism, are suspected to be severely injured. Materials and Methods: A total of 134 consecutive trauma patients with an ISS ≥ 16 adm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…When an experienced technician performs this scan, the sensitivity of the ultrasound compared to a conventional angiographic scan as a reference technique is 90% to 95% for lesions that require interventional treatment. This examination may omit lesions with preserved flow, such as intimate denudation or pseudoaneurysms [19][20][21][22][23]. In our study, the Doppler ultrasound had a sensitivity of 70% and a specificity of 55% and was shown in 10 patients out of 106 with injuries caused by accidental mechanisms.…”
Section: Discussionmentioning
confidence: 63%
“…When an experienced technician performs this scan, the sensitivity of the ultrasound compared to a conventional angiographic scan as a reference technique is 90% to 95% for lesions that require interventional treatment. This examination may omit lesions with preserved flow, such as intimate denudation or pseudoaneurysms [19][20][21][22][23]. In our study, the Doppler ultrasound had a sensitivity of 70% and a specificity of 55% and was shown in 10 patients out of 106 with injuries caused by accidental mechanisms.…”
Section: Discussionmentioning
confidence: 63%
“…Figure 1 shows a clinical application with therapy-relevant information gained through MRI. In a previous paper, we were able to demonstrate the benefit of this imaging in the context of cervical vascular diagnostics and recommended the implementation of this imaging option [ 10 ] in clinical routine. This approach is reinforced by Yamada et al, who proposed a concept of early MRI diagnostic in suspected lesions of cervical vessels, allowing an earlier administration of treatment, which, in turn, contributes to a good clinical outcome [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…We, for now, recommend sagittal T1, T2, and T2 STIR plus axial T2 in suspected spine trauma. For cervical artery dissections, axial PD and T1 fat-sat plus contrast-enhanced MR-angiography and/or time-of-flight MR-angiography, especially for dissections near or within the skull base, revealed a lot of dissections in a step-up approach [ 10 ]. Fast whole-body sequences, e.g., DWIBS (diffusion-weighted imaging with background suppression), should be evaluated as an add-on for patients undergoing spine MRI anyways or for child trauma MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on an analysis of a trauma registry, the authors successfully validated mTICCS against well-established and more sophisticated algorithms and found that it presents an useful tool to predict the need for massive transfusion early [2]. Focusing on neurological aspects (D-problem), Popp et al validated a CT protocol with mandatory dedicated computer tomography angiography (CT-A) to detect cervical artery dissections in severely injured patients [3]. From the results of their monocentric, prospective study, the authors concluded that their imaging pathway is likely to reduce possible therapeutic delays.…”
mentioning
confidence: 99%